Kajian Kitab Tafsir `Ali Ash-Shobuni Row - Zaini, M.; Basori (Faculty Ushuluddin, Adab, and Dakwah Institut Agama Islam Negeri (IAIN) Palangka Raya, 2025)
The Rowâi`u Al-Bayân Tafsîr Âyât Al-Ahkâm Min Al-Qurân by Sheikh `Ali Ash-Shobuni is a monumental contribution to the study of Quranic exegesis, particularly in interpreting legal verses. Combining traditional and modern approaches, this work provides an in-depth analysis encompassing linguistic, historical, and contextual aspects. Its systematic methodology harmonizes classical and contemporary interpretations, making the text highly relevant to addressing modern challenges. This tafsir not only enriches Islamic literature but also serves as a vital guide for scholars and the broader Muslim community.